2009
DOI: 10.1143/jpsj.78.044710
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting State of the Binary Boride Ru7B3 with the Noncentrosymmetric Crystal Structure

Abstract: Single crystals of Ru 7 B 3 were grown by the Czochralski puling method in a tetra-arc furnace. The compound crystallizes in a Th 7 Fe 3 -type structure (hexagonal, space group: P6 3 mc), which has no inversion symmetry along the c-axis. Measurements in magnetic fields indicate type-II superconductivity with upper critical fields of H c2 ð0Þ ' 17:2 kOe for H k ½001 and 15.8 kOe for H k ½100, respectively. The coherence length ð0Þ GL , penetration depth ð0Þ GL , and Ginzburg-Landau (GL) parameter ð0Þ obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
32
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 35 publications
11
32
2
Order By: Relevance
“…The dot line represents the WHH fitting, which shows a clear deviates from WHH prediction [12]. Because the invalidity of using the WHH theory, we have estimated the upper critical field through of the Ginzburg-Landau (GL) theory [13][14][15] (solid line), where…”
Section: Resultsmentioning
confidence: 99%
“…The dot line represents the WHH fitting, which shows a clear deviates from WHH prediction [12]. Because the invalidity of using the WHH theory, we have estimated the upper critical field through of the Ginzburg-Landau (GL) theory [13][14][15] (solid line), where…”
Section: Resultsmentioning
confidence: 99%
“…CePt 3 Si [1] has attracted great attention of condensed matter physics community. Similarly, some other noncentrosymmetric superconductors have been studied in recent past with conventional superconducting behavior such as Ru 7 B 3 , Mg 10 Ir 19 B 16 , α-BiPd, and the cubic phases of Re 3 W, and Re 24 Nb 5 [2][3][4][5][6][7]. Further, superconductivity has been reported in ntype metallic interface being formed between the LaAlO 3 and SrTiO 3 interface, which is naturally an inversion symmetry system without up-down reflection [8].…”
Section: Introductionmentioning
confidence: 98%
“…In fact theoretical studies predict heavy fermion as well as the unconventional Cooper pairing for these new superconducting materials [17]. Interestingly, yet the experimental studies on noncentrosymmetric materials did not displayed heavy fermion features and rather conventional superconductivity with small spin-orbit scattering is seen [2][3][4][5][6][7]. A recent scanning tunnelling microscopy (STM) study on noncentrosymmetric BiPd superconductor confirmed the same to be a single gap, s-wave superconductor [18].…”
Section: Introductionmentioning
confidence: 99%
“…The superconducting properties of several weakly correlated NCS systems have been extensively investigated, with notable examples such as: Li2(Pd,Pt)3B, Y2C3, Mg10Ir19B16, Ru7B3, LaIrP, Mo3Al3C, and with particular interest for this work LaNiC2. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] A large series of rare-earth (R) carbides RNiC2 and RCoC2 crystallize in the NCS CeNiC2 prototype structure, which is in the base centered orthorhombic space group Amm2. 30 These compounds generally display magnetic order arising from the 4f electrons confined to the rare earth sites, 31 in addition to the series being near a charge density wave (CDW) instability.…”
Section: Introductionmentioning
confidence: 99%